Gaucher disease: expression and characterization of mild and severe acid beta-glucosidase mutations in Portuguese type 1 patients - Amaral, O. (2011)
Type 1 Gaucher disease (GD), the most prevalent lysosomal storage disease, results from the deficient activity of acid alpha-glucosidase. Molecular analysis of 12 unrelated Portuguese patients with type 1 GD identified three novel acid â-glucosidase mutations (F109V, W184R and R395P), as well as three previously reported, but uncharacterized, lesions (R359Q, G377S and N396T). The type 1 probands were either heteroallelic for the well-characterized common lesion, N370S, and the F109V, W184R, R359Q or N396T lesions or homoallelic for the G377S or N396T mutations. Expression of the W184R, R359Q, and R395P mutations revealed very low specific activities based on cross-reacting immunologic material (CRIM SAs of 0.0004, 0.016 and 0.045, respectively), consistent with their being found only in type 1 patients who had a neuroprotective N370S allele. In contrast, the F109V, G377S and N396T alleles had significant acid â-glucosidase activity (CRIM specific activities of 0.15, 0.17, 0.14, respectively), in agreement with their being mild type 1 alleles. Thus, these studies identified additional acid â-glucosidase mutations in the Portuguese population and demonstrated that the G377S and N396T mutations were neuroprotective, consistent with the mild clinical phenotypes of the type 1 patients who were homoallelic for the G377S and N396T lesions.